The Spalding Suite. - Ellams, Inua (Oberon Books, 2015)
When we were young, we worshipped stars, gleaming long-limbed gods framed in the act of impossible flight. For a time we tried to follow, to carve out our own piece of sky with a butter-smooth arc of an arm and a Spalding ball glued to the fingertips ... Seen from a British perspective, The Spalding Suite gets to the heart and soul of the gravity-defying game and delves into the hopes and dreams of those who play it. From the fleeting high of the score and the robust camaraderie of the team, to the poignant lows of a body too worn to play the game.